Determinan Kecurangan Pelaporan Keuangan Dengan Komite Audit Sebagai Variabel Moderasi Pada Perusahaan Non Keuangan Di BEI 2019-2023 - Putu Fany Nadila Permata Sari Sari; Gede Adi Yuniarta; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2025)
This study aims to analyse the effect of audit quality, auditor switching and shareholding on the financial reporting of non-financial companies on the IDX in 2019-2023 with the audit committee as a moderating variable. The population of this study was 513 non-financial companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample was selected using the purposive sampling method to obtain 175 companies. The number of observations in this study was 875 from 175 companies over 5 years. The data analysis technique was logistic regression analysis with the MRA approach assisted by the IBM SPSS version 25 application. The results of the study indicate that audit quality has a negative effect on fraudulent financial reporting, auditor switching has a positive effect on fraudulent financial reporting, shareholding has a significant effect on fraudulent financial reporting, the audit committee cannot moderate the effect of audit quality on fraudulent financial reporting, the audit committee cannot moderate the effect of auditor switching on fraudulent financial reporting, and the audit committee can moderate the effect of majority shareholding on fraudulent financial reporting. Keywords: audit quality, auditor switching, majority shareholding, audit committee, financial reporting.